Chemical Composition and Anti-candida Activity of Trachyspermum ammi Essential Oil on Azoles Resistant Candida albicans Isolates from Oral Cavity of HIV+ Patients - I Ashrafi Tamai; T Zahraei Salehi; AR Khosravi; A Sharifzadeh; A Balal (Institue of Medicinal Plants, ACECR, 2013)
Background: Oral candidiasis, caused by Candida albicans, is one of the most common infections in immunocompromised patients, especially in HIV+ individuals. Objective: The aims of this study were to evaluate the susceptibility of C. albicans isolates to azole drugs and Trachyspermum ammi essential oil. Methods: Oral swabs were cultured from 70 HIV+ patients and In order to identify and confirm of C. albicans isolates, Chrom agar, Corn meal agar, germ tube production, carbohydrate assimilation, growth at 45˚C and PCR were performed. Sensivity to fluconazol, ketoconazole and clotrimazol were assessed by disc diffusion and also the effect of T. ammi essential oil was determined by disc diffusion and microdilution broth methods. Results: The causative agent, in 50 patients with oral candidiasis, was C. albicans (71.4%). In sensivity determination survey to antifungal drugs, the resistance of isolates to fluconazole, ketoconazole and clotrimazole were determined 32%, 28% and 14%, respectively. In disc diffusion, all isolates have an acceptable sensivity at 10 - 20 μL of the oil and 30 μL inhibit the growth completely in plate. Minimum Inhibitory Concentrsation (MIC) by microdilution broth method was 500ppm and 750ppm in 72% and 28% of isolates, respectively, and Minimum Fungicidal Concentration(MFC) in 70% of isolates were 750ppm and for the rest of the isolates (30%) were 1000ppm. Conclusion: We conclude that use of this native plant, as an antifungal compound, could act as a treatment of the patients with mucosal candidiasis, beside of other drugs in to the future.